Chitosan nanoencapsulation of Turbinaria triquetra metabolites in the management of podocyturia in nephrotoxic rats - Abdullah Abdel-Aal; Abdel-Aziz A. F.; Zakaria El-khayat; Nadia Mohamed; Merit Rostom; Emad Tolba; Nihal Galal El-Din Shams El-Din; Walaa S. A. Mettwally; Abdelhamid Aly Hamdy (Scientific Reports)
Abstract Cisplatin is a chemotherapeutic drug, which exhibits undesirable side effects. Chitosan nanoparticles are promising for drug delivery. The aim of this study was to determine the effect of the brown alga Turbinaria triquetra ethyl acetate fraction and polysaccharides, either loaded on chitosan nanoparticles or free, against podocyturia and cisplatin nephrotoxicity in rats. Sixty-six male rats were distributed into 11 equal groups: untreated control, chitosan (CSNPs), ethyl acetate fraction (EAE), polysaccharide (PS), EAE loaded on chitosan nanoparticles (EAE-CSNPs), PS loaded on chitosan nanoparticles (PS-CSNPs), Cisplatin or cis-diamminedichloroplatinum(II) (CDDP), CDDP + EAE, CDDP + PS, CDDP + EAE-CSNPs, and CDDP + PS-CSNPs. Serum urea, creatinine, creatinine clearance, renal malondialdehyde, nitric oxide, paraoxonase 1, renal nephrin, and podocin, and their renal mRNA gene expressions, as well as urinary nephrin and podocin were determined. The results indicated that the ethyl acetate fraction and polysaccharides, either free or loaded, efficiently attenuated podocyturia and cisplatin nephrotoxicity compared to the Cis group. However, the improvement was higher in the nephrotoxic groups treated with EAE-CSNPs and PS-CSNPs. The current study revealed that chitosan nanoencapsulation showed ameliorative effects against podocyturia and cisplatin nephrotoxicity in rats compared to free extracts, offering a new therapeutic strategy for attenuating podocyturia and CDDP-induced nephrotoxicity.